Redescription of the sea urchin Eucidaris thouarsii (Cidaroida: Cidaridae) based on material from the Mexican Pacific - Ruiz-Nava, Mariana-P.; Conejeros-Vargas, Carlos-A.; Solís-Marín, Francisco-A. (Revista de Biología Tropical, 2021)
Introduction: Eucidaris thouarsii is a cidaroid sea urchin found from the Gulf of California to Ecuador. Its taxonomy is based on general descriptions of test shape, primary and secondary spines, the Aristotle’s lantern, apical system, and peristome. Objective: To redescribe E. thouarsii with detailed descriptions, adding new taxonomic characters. Methods: We examined and reidentified 792 specimens, measuring and analyzing in detail structures of taxonomic value. Results: The horizontal diameter of the test ranges from 2.8 to 48.45 mm; the peristome corresponds to 40-60 % of that diameter, proportionally bigger than the apical system; the interambulacral areas are four times larger than the ambulacral areas. The variation of the pedicellariae is shown with scanning electron microscopy. The specimens of the Mexican oceanic islands are markedly different when compared to those of the mainland. Conclusions: Eucidaris thouarsii has five well differentiated secondary spines, and also specific regionalization; the apical system varies according to the size of the Horizontal Diameter of the Test; the globiferous pedicellariae have intraspecific differences; and the tridentate pedicellariae are specifically regionalized.